Microvascular endothelial function in a multi-ethnic group of apparently healthy South African men and women: Implications for testing and the relationship between insulin resistance and microvascular reactivity - Pienaar, Paula Roxana (Department of Human Biology, 2015)
Endothelial dysfunction is associated with cardiovascular disease risk factors and precedes structural changes in the blood vessels that occur prior to clinical manifestations. Measuring ethnic differences in microvascular endothelial function will provide insight into the disparate cardio-metabolic disease profiles that exist within a multi-ethnic South African population. Moreover, it has been shown that insulin resistance is associated with microvascular endothelial dysfunction in obese persons4, but it is unclear whether this relationship is mediated by body fat in apparently healthy individuals with and without insulin resistance. To our knowledge this has not been done in a South African population. Aims: The overall aim of this thesis was to measure microvascular endothelial function using Laser Doppler Imagery (LDI) and iontophoresis of acetylcholine (ACh) and sodium nitroprusside (SNP) in a multi-ethnic, apparently healthy group to determine whether: 1) there are ethnic differences in microvascular endothelial function and 2) whether the association between microvascular endothelial function and insulin resistance (IR) is independent of body fat in women with and without IR.